2015
DOI: 10.2217/fmb.15.132
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccination: Acceptance and Influencing Factors Among Young Men in Germany

Abstract: Our results demonstrate a high acceptance of male HPV vaccination. Education about HPV infection is low and should be intensified by medical professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…Although several questionnaire surveys about HPV prevention among Japanese mothers have been reported, these previous studies did not include questions about male involvement in HPV prevention or about whether boys and men should also be vaccinated, and only a few surveys researching the awareness of HPV prevention have focused on men . A study that targeted 27 fathers living in Japan found that they had poor knowledge but a high acceptance of HPV vaccination, similar to our findings.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although several questionnaire surveys about HPV prevention among Japanese mothers have been reported, these previous studies did not include questions about male involvement in HPV prevention or about whether boys and men should also be vaccinated, and only a few surveys researching the awareness of HPV prevention have focused on men . A study that targeted 27 fathers living in Japan found that they had poor knowledge but a high acceptance of HPV vaccination, similar to our findings.…”
Section: Discussionsupporting
confidence: 84%
“…The authors of this previous work stressed the importance of active male involvement in CC prevention strategies. Another questionnaire study examined attitudes toward HPV vaccination among 378 German men, finding that approximately 74% of these men wanted to be inoculated with the vaccine . A questionnaire study of 14–24‐year‐old boys and men in Italy found that 58.2% of nonvaccinated participants were willing to receive the vaccine .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The rst part included 4 questions related to students' demographic data: gender, age range, graduation year attendance, and university geographical macroarea. The second part consisted of 48 statements and aimed to investigate the students' knowledge of HPV + cancer (statements 1-18), infection (statements [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and vaccines (statements [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. For this part, "true"/"false" dichotomous responses were used (Figs.…”
Section: Description Of the Questionnairementioning
confidence: 99%
“…However, there is still a large proportion that gathers their information about medical issues when visiting their doctor. However, when young men are asked about their level of information regarding HPV, over 90% state that they have never been informed by their primary care physician [19]. Updated knowledge and positive attitude towards the vaccine are shown to be the main determinant factors for recommendation of vaccination among physicians [20,21].…”
mentioning
confidence: 99%